Mid-infrared luminescence and energy transfer of Tm3+ in silicate glasses by codoping with Yb3+ ions. (1st September 2017) - Cao, Ruijie; Lu, Yu; Tian, Ying; Huang, Feifei; Guo, Yanyan; Xu, Shiqing; Zhang, Junjie
Highlights: The optimized concentration ratio of Tm 3+ and Yb 3+ was found to be 1:3. The energy transfer efficiency from Yb 3+ to Tm 3+ could reach 90.94%. The absorption coefficient αOH − is decreased 0.527 cm −1 . The stimulated emission cross section is as high as 2.51 × 10 −20 cm 2 . Abstract: A kind of novel silicate glasses doped with Tm 3+ sensitized by Yb 3+ were prepared by conventional melt quenching method. The optical properties of the synthesized glasses were theoretically and experimentally investigated. Based on the absorption spectra and the Judd-Ofelt theory, the J-O intensity parameters (Ωt ), radiative transition probability (400.4 s −1 ), fluorescence lifetime (4.99 ms) and absorption and emission cross sections (σe = 2.51 × 10 −20 cm 2 ) were calculated. According to fluorescence spectra, the 1.8 μm emission of Tm 3+ could be greatly enhanced by adding proper amount of Yb 3+ under the excitation of 980 nm and the optimized concentration ratio of Tm 3+ and Yb 3+ was found to be 1:3 in the present silicate glass system. Besides, the energy transfer mechanism between Yb 3+ and Tm 3+ were thoroughly discussed. With the assistance of Yb 3+, the lifetime of Tm 3+ from 0.54 ms increased to 1.42 ms. The energy transfer efficiency from Yb 3+ to Tm 3+ could reach 90.94%, and the energy transfer coefficient was 5.43 × 10 −41 cm 6 /s. The content of OH − was measured. The above results showed that Tm 3+ /Yb 3+ co-doping could be expected to a promising way to achieve high efficient 2 μm lasing pumped by a 980 nm LD.